2006
DOI: 10.1159/000093524
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Recognition Memory, Conscious Recollection, and Executive Function in Patients with Schizophrenia

Abstract: Background: Dual-process models propose that recognition memory (RM) involves two processes: conscious recollection and familiarity-aware memory. Studies investigating RM in schizophrenia report a selective deficit in conscious recollection and intact levels of familiarity-driven RM for stimuli presented in the visual and olfactory domains. It has been suggested that abnormalities in conscious recollection result from a breakdown in frontal strategic memory processes involved in encoding and retrieval and exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Conversely, no SM deficits have been reported for conditions where self is preserved, such as major depressive disorder. 34 However, deficits in ISM, but not RM, have been also encountered in patients with obsessive-compulsive disorder, 47 requiring caution in interpreting SM findings as specific for self-disturbances until replicated results from cross-diagnostic studies are available.…”
Section: Source Monitoring and Hallucinationsmentioning
confidence: 99%
“…Conversely, no SM deficits have been reported for conditions where self is preserved, such as major depressive disorder. 34 However, deficits in ISM, but not RM, have been also encountered in patients with obsessive-compulsive disorder, 47 requiring caution in interpreting SM findings as specific for self-disturbances until replicated results from cross-diagnostic studies are available.…”
Section: Source Monitoring and Hallucinationsmentioning
confidence: 99%
“…Articles reporting number of categories achieved and perseverative errors in SCZ, REL, and HC were included. Effect sizes were calculated and reported on a total of 41 articles (38 categories achieved: Altshuler et al, 2004; Battaglia et al, 1994; Braff et al, 1991; Cadenhead et al, 1999; Condray et al, 1999; Dieci et al, 1997; Drakeford et al, 2006; Egan, Goldberg et al, 2001; Franke et al, 1992; Glahn et al, 2000; Gold et al, 1997; Goldberg et al, 1998; Gooding et al, 1999; Gooding and Tallent, 2002; Gooding et al, 2001; Haut et al, 1996; Hoff et al, 1992; Hoff et al, 1998; Josman and Katz, 2006; Keefe et al, 1994; Keri et al, 2001; Laurent et al, 2000; Laurent et al, 2001; Merrin et al, 2006; Morrens et al, 2006; Perry and Braff, 1998; Rybakowski and Borkowska, 2002; Seidman et al, 1991; Shum et al, 2004; Snitz et al, 1999; Stratta et al, 2003; Stratta, Daneluzzo, Mattei et al, 1997; Stratta, Daneluzzo, Prosperini et al, 1997; Suhr, 1997; Sullivan et al, 1993; Tallent and Gooding, 1999; Toomey et al, 1998; Wolf et al, 2002; and 30 perseverative errors: Altshuler et al, 2004; Battaglia et al, 1994; Condray et al, 1999; Dieci et al, 1997; Drakeford et al, 2006; Egan, Goldberg et al, 2001; Glahn et al, 2000; Gold et al, 1997; Gooding et al, 1999; Gooding and Tallent, 2002; Gooding et al, 2001; Haut et al, 1996; Josman and Katz, 2006; Keefe et al, 1994; Keri et al, 2001; Laurent et al, 2000; Laurent et al, 2001; Merrin et al, 2006; Rybakowski and Borkowska, 2002; Scarone et al, 1993; Shum et al, 2004; Snitz et al, 1999; Stratta, Daneluzzo, Mattei et al, 1997; Stratta, Daneluzzo, Prosperini et al, 1997; Suhr, 1997; Sullivan et al, 1993; …”
Section: Neuropsychological Measuresmentioning
confidence: 99%
“…For example, 16 of 19 studies reported that recollection was reduced in schizophrenia patients relative to demographically matched controls (10-19, 21-23, 25-27), whereas only three (1 PD and 2 RKN) found no significant group differences (20, 24, 28). In contrast, when familiarity was examined, seven studies (1 PD, 3 ROC, 3 RKN) indicated that familiarity was reduced (22-28), seven (all RKN) that familiarity was unaffected (11, 14-17, 20, 21), and five (all RKN) that familiarity was increased, rather than decreased (10, 12, 13, 18, 19), in patients with schizophrenia. These mixed conclusions regarding familiarity may reflect the fact that there is more heterogeneity in the effects of schizophrenia on familiarity versus recollection.…”
Section: Introductionmentioning
confidence: 99%